SEX-SPECIFIC DIFFERENCES IN RISK FACTORS AND THEIR CORRELATION IN PATIENTS WITH ESSENTIAL HYPERTENSION (STAGE III) - Lyubov N. Korichkina; Viktoria N. Borodina; Olga B. Poselyugina (Кубанский научный медицинский вестник, 2019)
Aim. This paper is aimed at identifying risk factors (RFs) and assessing their correlation in men and women with essential hypertension (stage III) under medical treatment. Materials and methods. Ninety-eight patients (45 men and 53 women) with essential hypertension (stage III) were examined. All of them were divided into two groups by sex. Both groups were studied for risk factors (age, disease duration, body mass index), as well as the following indicators: blood lipids; blood glucose; total bilirubin and its fractions; alanine aminotransferase (ALT); aspartate aminotransferase (AST); blood creatinine with the calculation of glomerular filtration rate (GFR) using MDRD and CKD-EPI equations. Results. Sex-specific differences in RFs and their correlation in patients with essential hypertension (stage III) are presented. The frequency of comorbid pathology and associated conditions, as well as the amount of medication used by men and women is shown. Conclusion. Women are diagnosed with essential hypertension 4 years earlier; BMI values correspond to Class 1 obesity; GFR level corresponds to Stage 3 of chronic kidney disease; whereas men have higher levels of direct bilirubin, ALT and blood creatinine. Comorbid pathology is significantly more common in women, with diabetes mellitus being the most commonly detected such a pathology. The risk factor correlation in men and women is different, having a statistically significant multidirectional correlative relationship. All of the considered issues require further systematic study, as well as a rational approach to the prescription of medical therapy and the risk factor correction, taking the patient’s sex into account.